The effects of marriage and divorce on women's nationality in Iranian law - Mohsen Hashemi Nasab Zavareh (Ius Humani. Jornal do direito, 2022)
Family as the first and foremost social institution greatly impacts its immediate larger society. Also the importance of family as a key figure in a healthy society, and the necessity of strong relations between spouses make it imperative to devise required legal devices. As women are prone to suffer and receive more damage in cases of family breakdown, the legislator should develop and establish more protective statutes in respect to the rights of women. In order to protect the rights of Iranian women, the legislator makes a distinction between the cases where an Iranian woman marries a foreign man, and those where Iranian men marry foreign women. In the former case, wife's change, or retention, of nationality is subject to the laws of the husband’s State while in the latter case the legislator enforces the unity of nationality principle. Marriage between Iranian women and foreign men causes women to experience a number of changes and limitations in terms of their national and inheritance rights. Also they may lose their Iranian nationality as a consequence of their marriage —in cases when the husband’s nationality, due to the law of the husband's State, is forced upon wife. On the other hand, foreign women married to Iranian men, though being forced to accept Iranian nationality, encounter less limitations resulting from marriage. Upon divorce, they are neither forced to accept a nationality, in contrast to the time when marriage is celebrated, nor denied their Iranian nationality. Thereby, they can choose whether to remain an Iranian national or recover their original nationality.